Presumption of innocence within the right to a fair trial: implementation and contradiction to pre-trial detention - Kudrjašova, Kristīna (Riga Graduate School of Law, 2023)
Being an integral part of the right to a fair trial, the principle of the presumption of innocence not only ensures that every suspect is considered innocent until proven guilty, but also regulates the way how public authorities approach the conduct of the criminal trial. Sometimes, however, there may be a need to place the suspected under pre-trial detention, which, contrary to the presumption of innocence, requires a high degree of suspicion of guilt. The lack of court practice on compatibility of pre-trial detention with the presumption of innocence puts in question if the two can coexist in criminal proceedings. This research, therefore, aims to examine both the presumption of innocence and pre-trial detention within the scope of the European Convention on Human Rights and determine if a contradiction between the two exists. By contrasting a theoretical study of the ECHR legislation and the court practice, the research will establish in which way the presumption of innocence can regulate or have a limiting effect on pre-trial detention, this way also figuring if a gap exists in the regulation of pre-trial detention by the ECHR.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Procedural law::Criminal procedure; right to a fair trial; European Convention on Human Rights; presumption of innocence